Empowering traditional weaving artisans through development communication structures in TTS regency - Agus Kuncoro; Sumardjo Sumardjo; Champion P Lubis; Ivanovich Agusta (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research was conducted referring to the theoretical elements of development communication, while the practical techniques used were not considered. The purpose of this study is to describe the conditions and problems faced by the community in Timor Tengah Selatan Regency (TTS), especially those who carry out people's weaving business and analyze the development communication that occurs in the TTS Regency community. Qualitative methods are used to interpret real-world social problems, including people's behavior, perceptions, and experiences. This study used secondary data. Researchers use dissertations, scientific journals, the internet, and data from related agencies to gather this data. Furthermore, the authors conducted direct interviews with a group of people's weaving craftsmen under the guidance of the Department of Trade, Industry, Cooperatives, and SMEs in the TTS Regency. This study found that development communication in an area has not yet led to empowerment. On the other hand, the dynamics of power between the elderly and the younger generation will continue to be a hallmark of society. Therefore, development communication must be carried out to facilitate the communication structure of different local cultures, and to encourage empowerment not only for parents but also for the younger generation.